Median Nerve Compression From a Nondisplaced Fracture of the Coronoid Process of the Ulna: A Case Report - Kent, Jeremy B. (SAGE Publications, 2010)
Median nerve neuropathy following an elbow injury is uncommon. When it occurs, understanding the median nerve distribution and anatomy is crucial for identifying the cause and for distinguishing cases that can be managed with observation as opposed to intervention. The consequences of misdiagnosis can result in permanent disability. Understanding the mechanisms of nerve injury will help the clinician anticipate prognosis and guide treatment. Stretch, transection, and compression of nerves may present similarly, but isolating the mechanism and the extent of injury can guide the treatment modalities and help predict the overall recovery. The case is a report of median nerve compression in a woman after a nondisplaced fracture of the coronoid process of the ulna. Despite the unique nature of the patient’s symptoms, the neuropathy resolved with “watchful waiting.” The location of the injury was a key component in identifying the cause of the neuropathy. It highlights the importance of identifying a cause; some cases will resolve without intervention. Clinicians should consider median nerve compression when presented with a patient experiencing neurologic symptoms following such a fracture.